2014
DOI: 10.1590/s1415-47572014000100016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the in vivo and in vitro genotoxicity of glyphosate isopropylamine salt in three different organisms

Abstract: There is considerable controversy with regard to the genotoxicity of glyphosate, with some reports stating that this compound is non-toxic for fish, birds and mammals. In this work, we used the comet assay to examine the genotoxicity of glyphosate isopropylamine (0.7, 7, 70 and 700 μM) in human lymphocytes, erythrocytes of Oreochromis niloticus and staminal nuclei of Tradescantia (4430) in vitro and in vivo. Cells, nuclei and fish that had and had not been exposed to 5 mM N-nitrosodiethylamine (NDEA) were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 27 publications
1
21
0
2
Order By: Relevance
“…Studies of glyphosate genotoxicity emphasize the occurrence of damage to the DNA strands that when not repaired nor the cell removed, can lead to cell mutations that are the start of biological onset of cancer [22] [23] [24] [25]. So far, epidemiological and experimental evidence shows that structural and numerical chromosomal aberrations (CAs) generated by genotoxic agents are involved in carcinogenesis [26].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of glyphosate genotoxicity emphasize the occurrence of damage to the DNA strands that when not repaired nor the cell removed, can lead to cell mutations that are the start of biological onset of cancer [22] [23] [24] [25]. So far, epidemiological and experimental evidence shows that structural and numerical chromosomal aberrations (CAs) generated by genotoxic agents are involved in carcinogenesis [26].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of between glyphosate and mitochondrial succinate dehydrogenase has been verified by molecular modeling (Ugarte, 2014). The IPA salt of glyphosate was indicated to be genotoxic at concentrations of 0.16-1.6 µg/ml on human lymphocytes, fish erythrocytes and plant staminal nuclei in vitro and in vivo (Alvarez-Moya et al, 2014). Glyphosate has also been shown to be able to disrupt regenerative diploid (DIMF) and triploid fin cell lines from the Oriental weather loach (Misgurnus anguillicaudatus) with cytotoxicity of LC 50 = 0.315 and 0.372 mg/ml, respectively.…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 93%
“…Our findings are in line with previous comet assay in vitro and in vivo animal studies with glyphosate, which reported its damaging potential for the DNA. In one study (69), in vitro treatment of human lymphocytes with 0.7-700 µmol L -1 of glyphosate led to a significant increase in tail length. In another study (70), exposure of non-dividing human lymphocytes to 0.5-580 μg mL -1 of glyphosate along with metabolic activation resulted in a significant increase in tail intensity only at 580 μg mL −1 (~3.4 mmol L -1 ), as established with the alkaline comet assay (70).…”
Section: Alkaline Comet Assaymentioning
confidence: 99%